2016
DOI: 10.1097/cco.0000000000000262
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and risk factors for venous thromboembolism in lung cancer

Abstract: Knowledge about the epidemiology, risk factors, and prognostic value of VTE in lung cancer could help to prevent thrombotic complications and improve management of patients with lung cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 36 publications
1
31
1
Order By: Relevance
“…There is evidence that disturbed hemostasis plays a role in the metastatic capacity of solid tumors [40]. Increased activation of the blood coagulation along with the subsequent fibrinolysis evidenced in our cohort of lung cancer patients by higher MP-TF activity and thrombin leads to elevated D-dimer levels in patients with ED, related to poor prognosis in several studies on patients with solid tumors, including lung cancer [41]. These observations are in line with the study by Zhang et al [42].…”
Section: Discussionsupporting
confidence: 89%
“…There is evidence that disturbed hemostasis plays a role in the metastatic capacity of solid tumors [40]. Increased activation of the blood coagulation along with the subsequent fibrinolysis evidenced in our cohort of lung cancer patients by higher MP-TF activity and thrombin leads to elevated D-dimer levels in patients with ED, related to poor prognosis in several studies on patients with solid tumors, including lung cancer [41]. These observations are in line with the study by Zhang et al [42].…”
Section: Discussionsupporting
confidence: 89%
“…It is well known that D-Dimer has been considered as a remarkable predictor associated with VTE in cancer including lung cancer [4, 5]. Interestingly, D-Dimer has been as well confirmed to be a similar predictor of lung cancer.…”
Section: Introductionmentioning
confidence: 98%
“…[3][4][5] Moreover, retrospective studies have reported associations between VTE and longer length of stay, higher rate of clinical complications, higher in hospital mortality rate, greater disability upon discharge, and more cost for various patients. [6][7][8] Thus, a method to estimate risk of developing VTE in patients with lung cancer will be clinically valuable. Several risk factors for cancer-related VTE have been identified, including cancer type, age, gender, bed rest, central venous catheter (CVC), anticancer treatment, and so on.…”
Section: Introductionmentioning
confidence: 99%
“…Several risk factors for cancer-related VTE have been identified, including cancer type, age, gender, bed rest, central venous catheter (CVC), anticancer treatment, and so on. 7,9 Although several VTE risk score system have been published in the recent years, they rely on biochemical predictors or are not lung cancer specific and thus provide limited clinical benefit. [10][11][12] Hence, the aim of this retrospective cohort study was to study clinical predictors of VTE in Chinese patients with lung cancer and to develop a scoring system to provide a reliable estimate of VTE risk.…”
Section: Introductionmentioning
confidence: 99%